2020
DOI: 10.1038/s41598-020-58101-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of 553 uncharacterized neurodevelopment patients reveals a high proportion of recessive pathogenic variant carriers in an outbred population

Abstract: A substantial portion of Mendelian disease patients suffers from genetic variants that are inherited in a recessive manner. A precise understanding of pathogenic recessive variants in a population would assist in pre-screening births of such patients. However, a systematic understanding of the contribution of recessive variants to Mendelian diseases is still lacking. Therefore, genetic diagnosis and variant discovery of 553 undiagnosed Korean patients with complex neurodevelopmental problems (KND for Korean Ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Re-evaluation of patients previously determined to be without pathogenic variants often allows for the discovery of new variants due to accumulating understanding of gene-disease relationships and improved bioinformatic pipelines ( Ewans et al, 2018 ; Epilepsy Genetics Initiative, 2019 ; Jalkh et al, 2019 ; Fung et al, 2020 ). Previous re-analysis studies have reported 5%–12% increases in diagnostic yield ( Ewans et al, 2018 ; Epilepsy Genetics Initiative, 2019 ; Jalkh et al, 2019 ; Fung et al, 2020 ); here, we observed a 5.9% increase in diagnostic yield, discovering pathogenic variants in 33 patients among the 553 that were previously analyzed in 2020 (KND553; Figure 1A ) ( Lee et al, 2020 ). The variants implicated in these 33 cases can be broadly divided into two groups, 1) variants for which new entries in OMIM allowed defining them as pathogenic ( n = 8; Table 1 ) and 2) pathogenic calls previously missed during the bioinformatic process ( n = 25; Table 2 ).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Re-evaluation of patients previously determined to be without pathogenic variants often allows for the discovery of new variants due to accumulating understanding of gene-disease relationships and improved bioinformatic pipelines ( Ewans et al, 2018 ; Epilepsy Genetics Initiative, 2019 ; Jalkh et al, 2019 ; Fung et al, 2020 ). Previous re-analysis studies have reported 5%–12% increases in diagnostic yield ( Ewans et al, 2018 ; Epilepsy Genetics Initiative, 2019 ; Jalkh et al, 2019 ; Fung et al, 2020 ); here, we observed a 5.9% increase in diagnostic yield, discovering pathogenic variants in 33 patients among the 553 that were previously analyzed in 2020 (KND553; Figure 1A ) ( Lee et al, 2020 ). The variants implicated in these 33 cases can be broadly divided into two groups, 1) variants for which new entries in OMIM allowed defining them as pathogenic ( n = 8; Table 1 ) and 2) pathogenic calls previously missed during the bioinformatic process ( n = 25; Table 2 ).…”
Section: Resultssupporting
confidence: 63%
“…In our previous study using 553 KND patients, we estimated that one in every 17 healthy individuals is a carrier for at least one pathogenic variant for a recessive genes represented in the KND cohort. This estimate remains unchanged using 1,180 patients ( Lee et al, 2020 ), but with a patient set twice as large, we inferred that the power to predict carriers would substantially increase. We first collected a list of pathogenic LoF and missense variants from ClinVar and KND, and aggregated their population frequencies using the gnomAD East Asian and Korean Variant Archive [KOVA 2; 5,305 healthy Korean individual set ( Lee et al, 2017 )].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Compared to populations higher burden of consanguinity, homozygous pathogenic variants in ROH are rarely found in an outbred population such as Koreans 40 . Rather, such regions can be used to signify a positive selection that was imposed on the population in the form of a selective sweep 41 .…”
Section: Regions Of Homozygosity and Positive Selectionmentioning
confidence: 93%